Efficacy of neurofeedback-assisted mindfulness for anxiety and nomophobia in Spanish young adults: a randomized controlled trial - Fernandez-Crespo, Mei; Rihuete-Galve, M. Isabel; Sanchez-Aguadero, Natalia; Sanchez-Sanchez, Nerea; Gonzalez-Sanchez, Jesus; Garcia-Yu, Irene A.; Lee, Hsin-Chien; Recio-Rodriguez, Jose I. (Frontiers in Public Health, 2025)
BackgroundProblematic use of new technologies has been associated with anxiety and other disorders in young adults. This study evaluated the efficacy of a Neurofeedback-Assisted Mindfulness Training Program (NAMTP) in reducing anxiety and related symptoms in young adults.MethodsA randomized clinical trial assigned participants to an intervention group (IG), receiving 20-25 NAMTP sessions, or a control group (CG). All participants received a brief workshop on responsible technology use. Anxiety was assessed using the DASS-21 anxiety subscale. Secondary outcomes included the Smartphone Addiction Scale—Short Version (SAS-SV), Nomophobia Questionnaire (NMP-Q), and Athens Insomnia Scale (AIS), all evaluated at baseline and three months.ResultsA total of 40 participants completed the study (82.5% women; mean age 24.8 ± 3.4). No statistically significant differences were observed between the intervention group (IG) and the control group (CG) in any of the psychological variables assessed. For the DASS scales, the mean differences (IG–CG) were 0.1 (95% CI: −1.6 to 1.9; p = 0.868) for anxiety, −2.4 (95% CI: −7.2 to 2.4; p = 0.324) for depression, and −1.5 (95% CI: −5.3 to 2.4; p = 0.453) for stress. Similarly, the mean difference in the SAS-SV score was −1.0 (95% CI: −5.0 to 2.9; p = 0.606), while for the NMP-Q score it was 3.7 (95% CI: −8.9 to 16.4; p = 0.553). Finally, the Athens Insomnia score showed a mean difference of −1.1 (95% CI: −2.9 to 0.7; p = 0.211). Adherence to the NAMTP program was high (88.8%).ConclusionsThe NAMTP did not produce significant improvements in anxiety, mobile phone addiction, nomophobia, or sleep quality. These findings suggest that, although NAMTP is feasible and well-tolerated, further research is needed to determine its potential benefits.Trial registrationClinicaltrials.gov; NCT06188910. http://www.Clinicaltrials.gov/ct2/show/NCT06188910.